Structurally controlled mineralization in parts of Aravalli craton, India: Constraints from gravity and magnetic data. (March 2023) - Babu, S. Bangaru; Satyakumar, A.V.; Kulkarni, Ajay Vinayak; Vats, Parijat Kishan
Abstract: Aravalli craton of central Rajasthan comprises Mangalwar Complex and Sandmata Complex with Archean to Proterozoic basement, well known for the mineralization. Recent geological studies have also revealed that the Aravalli mountains of the Banded Gneiss Complex are composed of Paleoproterozoic granulite and amphibolite-facies. Extensive geophysical surveys comprising gravity and magnetic were conducted to assess the occurrence of potential mineral sources in the uplifted crustal blocks of the Aravalli Fold belt. The calculated Bouguer gravity anomalies trending in a NE-SW direction and three broad gravity highs (∼7–10 mGal) were observed. These gravity highs may be due to the uplifting of the basement or the presence of high-density contrast material near the subsurface. A gradient in the gravity contours at the northwestern part of the study area is due to the fault/structural contact trending along the NE-SW direction. The 2D inversion technique is used to model the gravity data perpendicular to fault/contact. The horizontal gradient reflects the distribution of structures and intrusive bodies, which will give new insight for further future mineral exploration. The spectral analysis depicts the three depth interfaces, ∼7, ∼3.1, and ∼1.1 km, representing the basement and shallow depth interfaces. Further, the subsurface ore bodies geometry was obtained through 2D modelling of gravity data incorporating the constraints from the rock sample's physical property (density). We established that the structure and lithology of the host rocks were responsible for controlling mineralization by integrating the geochemical findings with geophysical measurements. In addition, the Archean to the Proterozoic basement of the study area is undulating at a depth of ∼3–5 km. Graphical Abstract: ga1 Highlights: The structural features linked with mineralization zones of the Aravalli Craton in India are extracted. Archean to the Proterozoic basement is undulating at a depth of ∼3–5 km. The mineralization at the Aravalli craton is controlled by the structural features and lithology of the host rocks